Environmental Policy, Mergers and Environmental R&D with Spillovers - Wang, Chenyu (2020)
This project lies at the frontier between environmental economics and industrial organization. We use a duopoly setting of a three-stage game; in the first stage, the government chooses an emission tax and aims for maximizing welfare; in the second stage, firms use R&D to reduce their emissions; in the last stage, firms compete a la Cournot with differentiated products. We focus on two policy regimes and three scenarios, namely regimes of competition and merger and scenarios of commitment, non-commitment, and exogenous tax. The study focuses on two major questions: (1) what is the effect of merger on R&D, and the effect of commitment on R&D? (2) what is the effect of merger and commitment on the economy? Results are obtained through numerical simulations of the model. We find that: (i) Merger has a positive effect on R&D under non-commitment and the exogenous tax scenarios. (ii) Under commitment, if goods are imperfect substitutes or homogenous, merger has a negative effect on R&D; if goods are complements or independent, merger has a positive effect on R&D. (iii) For any types of goods under any regime, commitment has a negative effect on R&D.